Vegetative propagation of Dalbergia tonkinensis, a threatened, high-value tree species in South-east Asia. Issue 3 (3rd July 2019) - Nhung, Nong Phuong; Thu, Pham Quang; Chi, Nguyen Minh; Dell, Bernard
Abstract : Dalbergia tonkinensis (Fabaceae) is one of the most valuable rosewood furniture species in the world. Although all species of Dalbergia are now included in Appendix II of the Convention on International Trade in Endangered Species of Wild Fauna and Flora, the threat from illegal harvesting remains. Plantation establishment of D. tonkinensis is in its infancy and requires the development of clonal propagation and nursery technology. Cutting experiments were therefore conducted to identify the efficacy of rooting hormones (IAA, IBA and NAA at 0.5, 1.0, 1.5 and 2.0 g L −1 ), rooting substrate (gravel, river sand and soil), season (spring, summer, autumn and winter), cutting length (10, 20 and 30 cm) and age of the mother tree (1, 5, 10, 15 and 20 years). Cuttings treated with IBA at a concentration of 1.5 g L −1 had the highest rooting percentage and number of roots, attaining 92.2% and 12.3 roots cutting −1 after 45 d, respectively. Rooting percentage and number of roots increased when cuttings were taken in spring and autumn, with the highest mean root length in spring. The rooting ability of cuttings was highest when collected from mother trees at 1 and 5 years old, after which the rooting ability decreased with age. The substrate did not affect the rooting percentage of cuttings but mean root numbers and mean root lengths of cuttings in river sand were higher than those in the other two substrates. Cutting length did not affect the rooting ability of D. tonkinensis cuttings. These results will be used to establish clonal propagation of superior mother trees for commercial and conservation planting of this threatened species in Vietnam.